المعالجة الشرعية للالتزامات المالية المحرمة على البنوك الأفغانية بعد تحولها إلى النظام المصرفي الإسلامي: دراسة فقهية تحليلية: The Shariah-Compliant Treatment of Prohibited Financial Obligations on Afghan Banks after Their Transition to the Islamic Banking System: An Analytical Jurisprudential Study - Tahir Sarfaraz, Mohammad; Sabri B Zakaria, Mohamad; Awang, Abdul Bari (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يهدف هذا البحث إلى معالجة أحد التحديات التي تواجه أسلمة البنوك، وهو الالتزامات المالية المحرمة التي نشأت نتيجة العمل في ظل النظام المصرفي التقليدي. وتكمن المشكلة في أن تصفية تلك الالتزامات تتطلب البحث عن البدائل والخطوات العملية للتغلب على هذا التحدي. وباستخدام المنهج الوصفي التحليلي، توصلت الدراسة إلى أن المقصود بالالتزامات المحرمة هنا هو كل ما استحقه الآخرون على المصرف بموجب عقود محرمة قبل التحول، مما يستوجب تجنب الوفاء بهذه الالتزامات بأي وسيلة مشروعة، حتى لو استلزم الأمر تحمل تعويضات مالية لفسخها والتخلي عنها. كما بينت الدراسة أن الودائع الجارية لا تحتاج إلى معالجة نظرًا لخلوها من الربا، وكذلك الاعتمادات المستندية إذا كانت مغطاة بالكامل. وفي المقابل، تتضمن الودائع الثابتة وودائع التوفير، والاعتمادات المستندية غير المغطاة، والسندات التزامًا بدفع فوائد ربوية على الديون، مما يستدعي التفاوض لإسقاط الربا وتحويل هذه الديون إلى صيغ تتوافق مع أحكام الشريعة الإسلامية. وفي السياق الأفغاني، أوضحت الدراسة أن الالتزامات المالية المحرمة لا تشكل عائقًا كبيرًا أمام عملية أسلمة البنوك التقليدية الأفغانية، نظرًا لأن أغلب الحسابات المصرفية كانت جارية، وخدمة الاعتمادات المستندية كانت محدودة، والبنوك لم تكن متورطة في إصدار السندات الربوية لعدم وجود سوق ثانوي للتداول. ABSTRACT This study aims to address one of the key challenges in the Islamization of banks, namely, the issue of prohibited financial obligations that have arisen due to operating under the conventional banking system. The problem lies in the fact that liquidating these obligations requires identifying alternatives and practical steps to overcome this challenge. Using the descriptive-analytical method, the study found that prohibited financial obligations in this context refer to all liabilities owed by the bank to others under contracts that violate Islamic principles before the transition. These obligations must be avoided by any possible means, even if it requires financial compensation to annul and disengage from them. The study also demonstrated that current deposits do not require restructuring since they are free from interest, as is the case with fully covered letters of credit. In contrast, fixed deposits, savings deposits, uncovered letters of credit, and bonds involve interest-bearing debt payments, necessitating negotiations to eliminate interest and restructure these debts into Shariah-compliant financing instruments. In the Afghan context, the study clarified that prohibited financial obligations do not constitute a significant barrier to the Islamization of Afghan conventional banks. This is mainly because most bank accounts in Afghanistan are current accounts, the use of letters of credit is limited, and banks have not been involved in issuing interest-bearing bonds due to the absence of a secondary market for trading such instruments.